Respuesta :
The given equation is [tex] -6x+18=-6 [/tex].
First add 6 to both sides of the equation,
[tex] -6x+18+6=-6+6\\
-6x+24=0 [/tex]
Add 6x to both sides of the equation,
[tex] -6x+24+6x=6x\\
24=6x\\
6x=24\\
x=\frac{24}{6} =4 [/tex]
The solution is [tex] x=4 [/tex]
Answer:
x=4
Step-by-step explanation:
We are given an equation -6x+18=-6
We need to solve for x
-6x+18=-6 ( Given )
Subtract 18 both sides ( Subtraction property of equality )
-6x+18-18=-6-18
Combine the like term both sides
-6x = -24
Divide by -6 both sides ( Division property of equality )
[tex]\dfrac{-6x}{-6}=\dfrac{-24}{-6}[/tex]
[tex]x=4[/tex]
The solution of the equation is x=4